2012
DOI: 10.1902/jop.2011.110365
|View full text |Cite
|
Sign up to set email alerts
|

Ridge Preservation With or Without an Osteoinductive Allograft: A Clinical, Radiographic, Micro‐Computed Tomography, and Histologic Study Evaluating Dimensional Changes and New Bone Formation of the Alveolar Ridge

Abstract: Test and control sites lost similar amounts of alveolar ridge, with the loss of buccolingual width occurring predominantly at the expense of the buccal bone. A thicker buccal plate was associated with less ridge loss in the vertical dimension. The percentage of new bone was not statistically significant between either the test or control sites, using either microCT or histologic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 22 publications
7
72
1
2
Order By: Relevance
“…Other studies have utilized micro‐CT to evaluate bone formation at grafted sites . It would have been possible to use micro‐CT to evaluate percentage of vital bone throughout the entire volume of the bone core in this current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have utilized micro‐CT to evaluate bone formation at grafted sites . It would have been possible to use micro‐CT to evaluate percentage of vital bone throughout the entire volume of the bone core in this current study.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been a result of using a resorbable collagen dressing without the same occlusive characteristics of other membranes popularly used for ridge preservation. The resorbable collagen dressing and cyanoacrylate were used in this study to provide initial stability for the wound and have been reported to be used in other ridge preservation procedures . By using the resorbable collagen dressing, any benefit in new bone formation could be attributed to the graft material itself.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of biomaterials, including autografts [9], allografts [10], xenografts [11], alloplastic materials such as bioactive glasses [12], autogenous tooth bone grafts [13][14][15], bioactive materials such as recombinant human bone morphogenetic protein-2 (rhBMP-2) [16], and platelet-rich fibrin (PRF) [17], has been shown to produce positive outcomes for ridge preservation. Autogenous bone is an ideal material for hard tissue defects because it has osteoinduction and osteoconduction and has no immune rejection.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Studies have shown that bone augmentation procedures with the use of bone graft materials may prevent progressive bone resorption. [15][16][17][18] Autogenous bone graft is considered the gold standard in regenerative procedures because it fulfills the 3 basic requirements for bone regeneration: osteogenesis, osteoinduction, and osteoconduction. Osteogenesis is the mechanism of bone growth from osteoblasts.…”
mentioning
confidence: 99%